Odpowiedzi

2010-01-25T20:13:58+01:00
1)
12x-7y=-16
x-3y=-68

x= -68 +3y
12 (-68+3y) - 7y= -16

x=-68+3y
-816 +36y - 7y=-16

x=-68 +3y
29y= 800

x=-68 +3y
y=27,58

x= -68 + 82,74
y= 27,58

x=14,74
y=27,58

2)4(x-2)-(y-2)=1
10x-2y=18

4x-8 -y +2 =1
10x-2y=18

-y=1-2+8-4x
10x-2y=18

y=-1+2-8+4x
10x-2y=18

y=-7+4x
10x - 2 (-7 +4x)= 18

y=-7 +4x
10x +14 - 8x = 18

y=-7+4x
2x=4

y=-7+4x
x=2

x=2
y=-7 + 8

x=2
y=1

3)x/2+y/3=1 1/3 /*6
x/3=y/2 = 2 1/3 /*6

3x+2y = 8 /*3
2x-3y=14 /*2

9x+6y= 24
4x - 6y = 28

13x=52
x=4

x=4
-6y= 28-16

x=4
-6y= 12

x=4
y=-2

Mysle, ze pomoglam i, ze tak jest dobrze. Pozdrawiam


2010-01-25T20:33:19+01:00
B)4(x-2)-(y-2)=1
10x-2y=18

4x-8-y+2=1
10x-2y=18

3x=1-2+8+y
10x-2y=18

3x=7+y/3 /:3
10x-2y=18

x=7/3 + y/3
10x-2y=18

x=7/3 + y/3
10(7/3 + y/3) -2y=18
70/3 +10y/3 - 2y =18 /*3
70+10y-6y=18
-4y=6-70
y=16

x=7/3 + 16/3 /*3
x=7+16
x=23

c)x/2 +y/3=1 1/3 /*6
x/3+y/2= 2 1/3 /*6

3x+2y=8
2x+3y=14

3x=8-2y /:3
2x=14-2y

x=8/3- 2y/3
2*(8/3 - 2y/3)=14-3y
16/3-4y/3=14-3y/*3
16-4y=51-9y
-4y+9y=51-16
5y=35
y=7

x=8/3-2*7/3
x=8/3-14/3
x=-2


a)12x-7y=16
x-3y=-68
x=-68+3y

12*(-68+3y)-7y=-16
816+36y-7y=-16
816+36y-7y=-16
29y=-16-816
29y=-832
y=- 832/29

x=-68+3*(-832/29)
x=2496/29- 68
x=154 2/29